Development of Ethnomathematics-Based Teaching Modules on the Nagekeo Tie Weaving Motif in Improving Learning Outcomes in Manungae Ndora Junior High School Students - Bertinsia Eku; Gregorius Taga; Ningsih (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
This study aims to produce ethnomathematics-based teaching modules on Nagekeo tie woven fabrics and to determine the effectiveness of ethnomathematics-based teaching modules on Nagekeo tie woven fabrics in improving learning outcomes. This type of research is Classroom Action Research (PTK) with a qualitative approach. This research was conducted at SMP Manungae Ndora class VIIA with a total of 21 students. Data collection techniques are carried out with test sheets, questionnaires and documentation. Student success indicators are marked by increasing student learning outcomes with KKTP 60 and student completeness reaching 70%. The results of research on the development of ethnomatemtics-based teaching modules on Nagekeo tie woven fabric can improve student learning outcomes. Increasing student learning outcomes are characterized by increased student activeness in following learning. The results showed that the effectiveness of students during the learning process using ethnomathematics teaching modules increased by 70%. Meanwhile, using ordinary teaching materials, students are less active and the percentage of learning is 60%. Based on the results of the study, it can be concluded that the use of ethnomathematics-based teaching modules can improve learning outcomes.